ECO-CREATIVE: PENGELOLAAN BOTOL KACA BEKAS UNTUK MEWUJUDKAN DESA BEBAS SAMPAH DAN PEMBERDAYAAN UMKM LOKAL - Agustina, Eka Santi; Latte, Jumai (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Processing organic waste, particularly used glass bottles, presents both a challenge and an opportunity in the effort to create a clean environment and empower the local economy. This community service activity aimed to raise awareness and enhance the skills of residents in Hantakan Village, South Kalimantan, in managing used glass bottles into economically valuable handicraft products. The methods employed included socialization, technical training, UMM workshops, and business mentoring. The results showed increased community participation in the collection and utilization of glass bottles, the formation of two local MSME (Micro, Small, and Medium Enterprises) groups, and the initial marketing of recycled products at the village and sub-district levels. This program demonstrates that the development of eco-creative initiatives can drive the creation of waste-free villages while opening up opportunities for creative and sustainable businesses, as well as strengthening market access so that local MSMEs can grow independently.